Autophagy induced by SAHA affects mutant P53 degradation and cancer cell survival. Issue 2 (19th February 2019) - Foggetti, Giorgia; Ottaggio, Laura; Russo, Debora; Mazzitelli, Carlotta; Monti, Paola; Degan, Paolo; Miele, Mariangela; Fronza, Gilberto; Menichini, Paola
Abstract : Missense mutations in the TP53 gene produce mutant p53 (mutp53) proteins which may acquire oncogenic properties favoring chemoresistance, cell migration, and metastasis. The exploitation of cellular pathways that promote mutp53 degradation may reduce cell proliferation and invasion as well as increase the sensitivity to anticancer drugs, with a strong impact on current cancer therapies. In the last years, several molecules have been characterized for their ability to induce the degradation of mutp53 through the activation of autophagy. Here, we investigated the correlation between autophagy and mutp53 degradation induced by suberoylanilide hydroxamic acid (SAHA), an FDA-approved histone deacetylase inhibitor. In the human cancer lines MDA-MB-231 (mutp53-R280K) and DLD1 (mutp53-S241F), SAHA induced a significant mutp53 degradation. However, such degradation correlated with autophagy induction only in MDA-MB-231 cells, being counteracted by autophagy inhibition, which also increased SAHA-induced cell death. Conversely, in DLD1 cells SAHA triggered a low level of autophagy despite promoting a strong decrease in mutp53 level, and autophagy inhibition did not change either mutp53 levels or sensitivity to this drug. We conclude that autophagy can be a relevant pathway for mutp53 degradation induced by SAHA, but its contribution to mutp53 destabilization and the consequences on cell death are likely context-dependent.